2021
DOI: 10.3390/rs13244968
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Soil Moisture Retrieval Procedure Based on the Integration of UAV Photogrammetry and Satellite Remote Sensing Information

Abstract: In countries characterized by arid and semi-arid climates, a precise determination of soil moisture conditions on the field scale is critically important, especially in the first crop growth stages, to schedule irrigation and to avoid wasting water. The objective of this study was to apply the operative methodology that allowed surface soil moisture (SSM) content in a semi-arid environment to be estimated. SSM retrieval was carried out by combining two scattering models (IEM and WCM), supplied by backscatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…We used the Excel app from Microsoft 365 along with SAS JMP Pro 16.1.0 for graphing and statistical analysis. Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Excel app from Microsoft 365 along with SAS JMP Pro 16.1.0 for graphing and statistical analysis. Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Because healthy vegetation with more chlorophyll reflects higher levels of light in the NIR and absorbs light in the red band, the NDVI distinguishes between areas of thick, healthy plant life vs. unhealthy and/or sparse plant life and has been used to both monitor plant health and drought conditions [49][50][51]. Researchers have shown that NDVI is directly related to the photosyn- Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…In recent years, the application of multispectral remote sensing technology in monitoring crop growth and analyzing soil characteristics has gradually increased [7][8][9][10][11]. In southern Africa, Ndlovu H S et al [12] utilized drone-based multispectral imagery to precisely estimate maize leaf water indices for crop monitoring and early warning system development, aiming to optimize agricultural production in smallholder farms.…”
Section: Introductionmentioning
confidence: 99%